2018
DOI: 10.1177/0898010118761401
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality, Spiritual Well-Being, and Spiritual Coping in Advanced Heart Failure: Review of the Literature

Abstract: It is marked by considerable suffering, for which palliative care has been recommended. Palliative care standards require the inclusion of spiritual care, but there is a paucity of literature supporting effective spiritual interventions for the heart failure population. A literature search resulted in 30 articles meeting the criteria for review of spirituality and spiritual coping in the heart failure population. Findings within this body of literature include descriptive evidence of the uniqueness of spiritua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 66 publications
(198 reference statements)
1
42
0
1
Order By: Relevance
“…Such associations are seen for both genders for mental health [6] as well as chronic and physical disorders [7]. A recent literature review shows these same benefits for individuals with HF [8]. Individuals with HF who report more daily spiritual experiences have higher existential well-being [9].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Such associations are seen for both genders for mental health [6] as well as chronic and physical disorders [7]. A recent literature review shows these same benefits for individuals with HF [8]. Individuals with HF who report more daily spiritual experiences have higher existential well-being [9].…”
Section: Introductionmentioning
confidence: 91%
“…A recent literature review shows these same benefits for individuals with HF [ 8 ]. Individuals with HF who report more daily spiritual experiences have higher existential well-being [ 9 ].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…[23,36,40] Spirituality is important for ascertaining health-related behaviors, attitudes and beliefs in patients with HF. [36,41,42] Bekelman et al stated that the mean FACIT-Sp scores of patients with HF were 37.0 and a better SWB was strongly associated with lower depression in their cross-sectional study. [36] Similar to this finding, the mean FACIT-Sp scores were 36.2 in our study, and we confirmed that there was a moderately negative correlation between the DASS and the FACIT-Sp scales in patients with HF.…”
Section: Discussionmentioning
confidence: 96%